The Effect of Marketing Mix and Product Quality on Consumer Satisfaction at Jempiring Bali in Bangli - Ni Luh Febriana Awidia PERTIWI; Ni Putu PERTAMAWATI; I Gusti Athina WULANDARI (Loka: Journal Of Environmental Sciences, 2024)
Purpose:Companies aim to satisfy consumers by understanding their needs and desires. One key to competitive success is continually creating new products and retaining customers through continuous innovation. This research aims to test and analyze the influence of marketing mix and product quality on consumer satisfaction.Methodology:This research was conducted in Jempiring, Bali, in Bangli with a research sample of 96 respondent taken using the Rao Purba formula. All data obtained from the questionnaire distribution are suitable for use, then analyzed using multiple linear regression, hypothesis testing (t test and F test).Findings:The research results show that (1) Marketing Mix and product quality have a significant effect on consumer satisfaction at Jempiring Bali in Bangli (2) Marketing Mix has a positive and significant effect on consumer satisfaction at Jempiring Bali in Bangli. This means that the better or improved ther marketing mix, the greater the consumer satisfaction at Jempiring Bali in Bangli. (3) Product quality has a positive and significant effect on consumer satisfaction at Jempiring Bali in BangliImplication:This means that other better or increased the quality products, the greater the consumer satisfaction at Jempiring Bali Bangli.